The Effect of Carbon Emission Disclosure and Environmental Costs on the Financial Performance of Energy Sector Companies on the Indonesia Stock Exchange in 2020-2024 - Stefan Timothy Lumbantobing; Nurmadi Harsa Sumarta (JURNAL ECONOMINA, 2026)
The increasing concerns over climate change and the growing demand for sustainable business practices have encouraged energy sector companies to enhance environmental transparency through carbon emission disclosure and environmental cost allocation. As one of the largest contributors to greenhouse gas emissions, energy companies face significant pressure from regulators, investors, and society to demonstrate their commitment to sustainability while maintaining financial performance. This study aims to examine the effect of Carbon Emission Disclosure and Environmental Costs on the Financial Performance of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employed a quantitative approach with a causal research design using secondary data obtained from annual reports and sustainability reports. The sampling process utilized purposive sampling, resulting in 108 observations after the elimination of outlier data. Financial performance was measured using Return on Assets (ROA), Carbon Emission Disclosure was assessed based on the GRI 305 index, and Environmental Costs were measured using the natural logarithm of total environmental expenditures. Data were analyzed using multiple linear regression supported by classical assumption tests, coefficient of determination analysis, F-test, and t-test. The results reveal that Carbon Emission Disclosure has a negative and significant effect on financial performance (t = - 5.965; p < 0.001), while Environmental Costs have a positive and significant effect on financial performance (t = 3.584; p < 0.001). The model explains 25.3% of the variation in financial performance. These findings indicate that the market still perceives carbon emission disclosure as an administrative burden that reduces short-term profitability, whereas environmental expenditures are viewed as strategic investments that enhance operational efficiency and create long-term economic value for firms.